PEMANFAATAN MEDIA SOSIAL SEBAGAI MEDIA PENYULUHAN AGAMA HINDU - I Gusti Ngurah Aan Darmawan; I Gede Sutana (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
Technological developments and the occurrence of social restrictions due to the COVID-19 pandemic have caused changes in various aspects of people's lives. This also has an impact on Hindu religious instructors in carrying out their duties as disseminators of dharma messages to sedharma people. The use of traditional methods in today's era cannot take place optimally. Therefore, the use of social media as a medium for Hindu religious education is very relevant. Apart from being easier to reach the public, relatively affordable costs and ease of conveying information are also positive things from the use of social media and Hindu religious instructors. The analytical method used in this study is literature study and document analysis related to the field of study, and describes it by means of interpretation and description analysis. In providing an analysis of the use of social media as a medium for counseling Hindu religion. The results and conclusions in this study are that in carrying out their duties, Hindu religious instructors have three important functions, namely: a) Informative and Educational Functions; b) Consultative Function; c) Advocative Function. Hindu religious instructors have six methods commonly used in spreading dharma teachings known as Sad Dharma, namely: a) Dharma Discourse; b) Dharma Tula; c) Dharma; d) Dharma Yatra; e) Dharma Sadhana; and f) Dharma Shanti. To answer the existing challenges and maximize the task of Hindu religious educators in the current era, social media is used as a means of disseminating dharma messages by Hindu religious educators, including: Youtube, Facebook, Instagram, and Tiktok.Keywords: Social Media, Hindu Religion Counseling